(untitled) - Stubblefield, Harold W. (San Francisco, 1994)
From the earliest contributions of Native Americans in the colonial period to the workforce preparation crisis in the 1980s, this book explores the patterns, themes, and changing ideologies of learning and education in adulthood.
Keywords: Adult education,Giáo dục người trưởng thành; History,Lịch sử; United States,Hoa Kỳ